IMPLEMENTASI PEMBELAJARAN AKIDAH AKHLAK DALAM PEMBENTUKAN KARAKTER SISWA DI MTS NEGERI 2 WONOSOBO - Rendi Setiyawan; Amliur Rohmah; Vina Izzatul Maliah; Nadifa Fadilah Al-Ayasy; Robingun Suyud El Syam (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the effectiveness of implementing Akidah Akhlak learning and the teachers’ strategies in internalizing Islamic moral values at MTs Negeri 2 Wonosobo. The research employs a descriptive qualitative approach, utilizing observation, interviews, and documentation as data collection techniques. The participants include the Akidah Akhlak teacher, school principal, and several students as supporting informants. Data were analyzed using Miles and Huberman’s interactive model, consisting of reduction, display, and conclusion drawing. The findings reveal that the implementation of Akidah Akhlak learning is effective in shaping students’ religious character, although challenges remain in terms of time allocation and methodological variation. The teacher’s main strategies include exemplary modeling, moral habituation, and value discussions. The key supporting factors are the school’s religious environment and strong institutional support. The study concludes that Akidah Akhlak learning at MTs Negeri 2 Wonosobo significantly contributes to the formation of students’ moral and spiritual character.